New methods and devices for investigation of the dura mater encephali and its processes. - S. S. Malakhov (Морфологія, 2016)
Background. The development of modern neuromorphology, neurosurgery and neurology requires a detailed study of neurovascular structures of the dura mater encephali and its processes. Objective. To determine the features of histological topography of blood supply and innervation of the dura mater encephali and its processes in people with individual anatomical variability of the head and skull. Methods. The survey was conducted on 30 specimens of dura mater encephali and its processes. Morphometry of neurovascular structures of dura mater and its processes was performed using new methods and devices developed by us. Results. New methods and devices that are necessary for a more detailed study of neurovascular structures of dura mater and its processes were developed, tested and implemented. Conclusion. First proposed and implemented in practice "Method for making total anatomical preparations of the tentorium cerebelli and its derivative venous structures", that allows to make comprehensive preparations of the native tent of the cerebellum and its derivative venous structures. Developed and tested new device designs: "Wet storage tank drugs membranes of the brain"; "The device for long-term storage of wet preparations of membranes of the brain "; "Device for the study of drugs konveksital wet surface dura mater of the brain"; "Device for the study of macroscopic basal neurovascular structures dura mater of the brain"; "Combination tool for the study of relationships neurovascular structures dura mater of the brain".